P. Allen Smith's bringing the garden indoors : containers, crafts, and bouquets for every room - Smith, P. Allen (Clarkson Potter/Publishers, 2009)
Garden designer P. Allen Smith is best known for the beauty he creates outdoors. Now, for the first time, he has turned his attention to the indoors. He shows how to choose the right containers for the greatest impact, decorate with the season in mind, pick unusual but visually dramatic props to complement a bouquet, or showcase a collection by using them as centerpieces for flowers and plants--From publisher description.